Neolithic sheep birth distribution: results from Nova Nadezhda (sixth millennium BC, Bulgaria) and a reassessment of European data with a new modern reference set including upper and lower molars - Balasse, Marie; Renault-Fabregon, Leo; Gandois, Henri; Fiorillo, Denis; Gorczyk, John; Bacvarov, Krum; Ivanova-Bieg, Maria (Journal of archaeological science, 2020)
During the course of the diffusion of Neolithic agro-pastoral societies across Europe, animal husbandry was adapted to local constraints and resources, involving changes in practices as well as in animal physiology. As a result, the timing of animal breeding was impacted, with consequences on the organization of agro-pastoral tasks and the seasonal availability of animal products. Past sheep birth seasonality can be investigated through the reconstruction of the seasonal cycle recorded in molars, based on the sequential analysis of stable oxygen isotope ratios (delta O-18) in enamel. Modern sheep serve as comparative material to define the season of birth. In the present study, we provide new reference values for winter births in the sheep third molar (M3) using data from the modern Kemenez sheep herd. The dataset also includes paired upper and lower M3s in order to test the comparability of results obtained from both teeth. Results show a moderate shift in the isotopic record between upper and lower M3s. The consecutive difference in the assessment of the timing of birth is one month, on average. Additionally, we provide a new set of results for sheep from Nova Nadezhda (Bulgaria, early sixth millennium BC), combining upper and lower molars, in order to expand data relating to the earliest stages of the introduction of sheep to Europe. At Nova Nadezhda, sheep were born in late winter and spring, and the pattern of birth distribution does not indicate the control of sheep reproduction by separating males from females. When compared to previously published results at other Neolithic and Chalcolithic sites in the Balkans, corrected for the shift between upper and lower M3s, no latitudinal and chronological trend is observed between the Southern Balkans, Northern Balkans and Hungarian plains over the early sixth to the second half of the fifth millennia BC. This apparent uniformity for the length (3-4 months) and timing of the birth period could be challenged in the future by enlarged datasets.